Experimental Studies of the Impact of the Geometric Dimensions of the Outlet Opening on the Effectiveness of Positive Pressure Ventilation in a Multi-Storey Building—Flow Characteristics - Piotr Kaczmarzyk; Paweł Janik; Daniel Małozięć; Wojciech Klapsa; Łukasz Warguła (Applied Sciences, 2023)
During rescue operations, one of the important parameters determining the effectiveness of the implementation of tactical mechanical ventilation is the selection of the appropriate size of the outlet opening. The objective of this article is to determine the effect of the size of the discharge opening area (0.24–1.2 m2) and other factors on the obtained flow parameters (flow velocity, volumetric flow rate and static pressure value) generated by the two tested positive pressure ventilators. The volumetric flow rate was determined by measuring the flow velocity at appropriately selected measurement points. Two ventilator units were tested (one was the conventional type, while two were turbo). During the tests, the fans generated a flow of 4624.17 m3/h to 14,020.92 m3/h (the first—conventional type) and 4884.66 m3/h to 15,656.33 m3/h (the second—turbo type). The analysis carried out in the article can be used as a guideline for designers of buildings, with particular emphasis on cases in which the staircase is not directly adjacent to the façade wall (an escape route built into the axis of the building).